New insights into the flavoring potential of cricket (Acheta domesticus) and mealworm (Tenebrio molitor) protein hydrolysates and their Maillard products. (1st December 2021) - Grossmann, Kora Kassandra; Merz, Michael; Appel, Daniel; De Araujo, Maria Monteiro; Fischer, Lutz
Highlights: Enzymatic hydrolysis of insect proteins develops savory and diverse taste profiles. Insect proteins hydrolysates and Maillard products show different sensory profiles. Identified odor-active molecules are also present in meat and seafood products. Insect proteins have potential for savory flavoring. Abstract: Insect proteins have an earthy-like flavor and have not shown great flavor potential for food applications so far. In this study, insect proteins of cricket Acheta domesticus and mealworm Tenebrio molitor larvae were first enzymatically hydrolyzed using two peptidase preparations (Flavourzyme1000L and ProteaseA "Amano"2SD). Xylose was then added to facilitate Maillard reactions (30 min, T = 98 °C, 1% (w/v) xylose). A comprehensive sensory evaluation showed that both the hydrolysis and the Maillard reactions changed the flavor description of the samples significantly to more complex and savory-like taste profiles (27 descriptors for cricket and 39 descriptors for mealworm protein). In addition, 38 odor-active molecules were identified using gas chromatography–olfactometry (1 alcohol, 5 acids, 11 aldehydes, 5 ketones and 16 heterocyclic compounds). The results showed impressively that the flavoring potential of insect proteins was significantly enhanced with respective processing.